Conclusion: Continues Improvements for Continues Attainments of POs - B. R., Dr. Arun Kumar (Handbook of Outcome-Based Education Model (OBE): Best Practices and Formats for OBE Implementation in Technical Higher Education Programs, 2023)
For continuous improvements of the program outcomes, consistent improvements/retention are essential concerning students’ admission, success rate, placements, higher studies, entrepreneurship, student-faculty ratio (SFR), faculty cadre proportion, faculty qualification, faculty retention, research and development and followed by PO attainments. In this connection, gaps identification and action thereof for each parameter mentioned above have to be taken care of by the concerned. In this Chapter Value added Courses (VACs) are seen as tools for filling the curriculum gap. The VACs are identified and designed based on the lack of PO attainments. This Chapter focuses on VACs and actions taken to improve PO attainments.